Imaginary number is one that when squared gives a negative result. ... With imaginary numbers, when you square them, the answer is negative. They are written like a real number, but with the letter i after them, like this: 23iThe letter i means it is an imaginary number.
Justin buys 4 hot dogs ad 5 pop corn boxes at the baseball game.
<h3>Equation</h3>
Equation is an expression which is used to show the relationship between two or more variables and numbers.
Let x represent the number of hot dogs and y represent the boxes of popcorn.
Justin buys a total of 9 snacks. Hence:
He buys popcorn 3 less than twice as many hot dogs. Hence:
Solving equations 1 and 2 simultaneously gives:
x = 4, y = 5
Justin buys 4 hot dogs ad 5 pop corn boxes at the baseball game.
Find out more on equation at: brainly.com/question/13763238
Well, I bet you want your answer right away! So here it is.
<span>Given <span>f (x) = 3x + 2</span> and <span>g(x) = 4 – 5x</span>, find <span>(f + g)(x), (f – g)(x), (f × g)(x)</span>, and <span>(f / g)(x)</span>.</span>
To find the answers, all I have to do is apply the operations (plus, minus, times, and divide) that they tell me to, in the order that they tell me to.
(f + g)(x) = f (x) + g(x)
= [3x + 2] + [4 – 5x]
= 3x + 2 + 4 – 5x
= 3x – 5x + 2 + 4
= –2x + 6
(f – g)(x) = f (x) – g(x)
= [3x + 2] – [4 – 5x]
= 3x + 2 – 4 + 5x
= 3x + 5x + 2 – 4
= 8x – 2
(f × g)(x) = [f (x)][g(x)]
= (3x + 2)(4 – 5x)
= 12x + 8 – 15x2 – 10x
= –15x2 + 2x + 8
<span>\left(\small{\dfrac{f}{g}}\right)(x) = \small{\dfrac{f(x)}{g(x)}}<span><span>(<span><span>g</span><span>f</span><span></span></span>)</span>(x)=<span><span><span>g(x)</span></span><span><span>f(x)</span></span><span></span></span></span></span><span>= \small{\dfrac{3x+2}{4-5x}}<span>=<span><span><span>4−5x</span></span><span><span>3x+2</span></span><span></span></span></span></span>
My answer is the neat listing of each of my results, clearly labelled as to which is which.
( f + g ) (x) = –2x + 6
( f – g ) (x) = 8x – 2
( f × g ) (x) = –15x2 + 2x + 8
<span>\mathbf{\color{purple}{ \left(\small{\dfrac{\mathit{f}}{\mathit{g}}}\right)(\mathit{x}) = \small{\dfrac{3\mathit{x} + 2}{4 - 5\mathit{x}}} }}<span><span>(<span><span>g</span><span>f</span><span></span></span>)</span>(x)=<span><span><span>4−5x</span></span><span><span>3x+2</span></span><span>
Hope I helped! :) If I did not help that's okay.
-Duolingo
</span></span></span></span>
Answer:
=AC or 7.8102=AC
Step-by-step explanation:
If we connect a line from point A to point C we create a triangle, and we can use pythagorean theorem to find this distance. So the line from point A to point C will be our hypotenuse and the other two distances will be out side lengths.
25+36=
61=
=AC or 7.8102=AC